Improved hearing protector attenuation through the use of a lubricant. - Ryan, Timothy J.; Meier, Rebecca S.; Tatarka, Ashley (Journal of Occupational & Environmental Hygiene, 2017)
A study of 40 novice hearing protection users was conducted to determine if the use of a lubricant with hearing protective plugs would enhance their attenuation. Three types of hearing protection devices (i.e., earplugs) were evaluated: roll-down PVC foam, mushroom-style polyurethane foam, and elastomeric flanged. For each earplug type, the right and left ear (dry and lubricated, respectively) personal attenuation rating was determined using a commercially available microphone in real-ear apparatus. Earplug efficacy was observed to increase in the presence of a lubricant for all 3 plug types, with average mean elevations by earplug type ranging from 1.5–5.1 dB. Two of three earplug types saw statistically significant improvements when used with lubrication, demonstrating heightened mean personal attenuation ratings of 2.8 dB and 5.1 dB. The issues of handedness and gender differences (vis à vis ear canal size) are explored, and the importance of proper fitting is discussed in detail. Several specific questions yet to be answered are posed, and directions for further research indicated.